Insurance and behavioral economics : improving decisions in the most misunderstood industry - Kunreuther, Howard; McMorrow, Stacey; Pauly, Mark V. , 1941- (Cambridge University Press, 2013)
"This book examines the behavior of individuals at risk, insurance industry decision makers and policy makers involved in the selling, buying, and regulating of insurance"-- Provided by publisher